2020
DOI: 10.48550/arxiv.2002.08507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adiabatic quantum pumping in buckled graphene nanoribbon driven by a kink

Dominik Suszalski,
Adam Rycerz

Abstract: We propose a new type of quantum pump in buckled graphene nanoribbon, adiabatically driven by a kink moving along the ribbon. From a practical point of view, pumps with moving scatterers present advantages as compared to gate-driven pumps, like enhanced charge transfer per cycle per channel. The kink geometry is simplified by truncating the spatial arrangement of carbon atoms with the classical φ 4 model solution, including a width renormalization following from the Su-Schrieffer-Heeger model for carbon nanost… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Earlier [15], we have shown that the system similar to the presented in Fig. 1 consisting of metallic graphene nanoribbon with armchair edges coupled to heavily-doped graphene leads may operate as efficient quantum pump, but the charge per cycle is not quantized.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Earlier [15], we have shown that the system similar to the presented in Fig. 1 consisting of metallic graphene nanoribbon with armchair edges coupled to heavily-doped graphene leads may operate as efficient quantum pump, but the charge per cycle is not quantized.…”
Section: Introductionmentioning
confidence: 92%
“…In attempt to improve electromechanical characteristics of such devices, one need to address fundamental issues concerning the structure of effective Hamiltonian at nanoscale, including tight-binding parameters [3], elastic coefficients [4,5], and electron phononcoupling [6]. Numerous works have addressed the idea of quantum pumping in graphene nanostructures [7][8][9][10][11][12][13][14][15], employing various physical mechanisms. These include gatedriven pumping [7,8], laser light [9], strain-induced fields [10], tunable magnetoresistance [11], quantum Hall states [12], but also electromechanical effects accompanying sliding Moiré patterns in twisted bilayer [13,14], or (most recently) moving kink in buckled graphene nanoribbon [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation